DNA-Assisted Dispersion of Multi-Walled CNTs in Epoxy Polymer Matrix. Issue 1700 (2014) - Laurenzi, Susanna; Sirilli, Matteo; Pinna, Mirko; Gabriella Santonicola, M.
ABSTRACT: The homogeneous dispersion of carbon nanotubes (CNTs) in a polymer matrix is a critical parameter that significantly affects the electrical and mechanical properties of CNT-based composite materials, and represents an important challenge to overcome during the manufacturing process of these materials. In our work we used double-stranded DNA to facilitate the dispersion of multi-walled CNTs in solution prior to the integration in epoxy resin PRIME 20 LV. Composites containing DNA-wrapped CNTs were prepared using sonication at 0.5 wt.% CNT loading and the dispersion level in the composite CNT/PRIME 20 LV was observed under an optical microscope. Nanoindentation experiments were conducted to determine the local mechanical properties of the CNT/PRIME 20 LV composites films after cure, showing a significant improvement in their distribution across the sample surface as a result of the enhanced CNT dispersion by DNA. An electrical test to assess the stability of the CNTs dispersion in the resin was developed by measuring the conductivity of the composite mixture before cure in time. Results of the electrical measurements indicate that the CNT/PRIME 20 LV mixture with DNA-wrapped CNTs is stable for several days after preparation.